Incremental Healthcare Service Utilization for Open-angle Glaucoma: A Population-Based Study. Issue 5 (June 2015) - Chung, Shiu-Dong; Ho, Jau-Der; Lin, Herng-Ching; Kao, Li-Ting; Tsai, Ming-Chieh
Abstract : Purpose: To investigate differences in the utilization of healthcare services between subjects with open-angle glaucoma (OAG) and comparison subjects without OAG using Taiwan's National Health Insurance population-based database. Patients and Methods: The study comprised 2204 subjects with OAG and 2204 sex-matched and age-matched subjects without OAG. We individually followed each subject for a 1-year period to evaluate their healthcare resource utilization. Outcome variables of the healthcare resource utilization were as follows: numbers of outpatient visits and inpatient days and the mean costs of outpatient and inpatient treatment. In addition, we divided healthcare resource utilization into ophthalmologic and nonophthalmologic services. Results: As for the utilization of ophthalmologic services, OAG subjects had significantly more outpatient visits (7.4 vs. 1.3, P <0.001) and significantly higher outpatient costs (US272 vs. US39, P <0.001) than comparison subjects. For nonophthalmologic services, OAG subjects also had significantly more outpatient visits (29.4 vs. 21.8, P <0.001) and significantly higher outpatient costs (US1263 vs. US847, P <0.001) than comparison subjects. Furthermore, OAG subjects incurred significantly higher inpatient costs compared with comparison subjects (US434 vs. US234, P <0.001). For all healthcare services, OAG subjects had significantly more outpatient visits (36.8 vs. 23.1, P <0.001) and significantly higher outpatient (US1535 vs. US887, P <0.001) and total (US2245 vs. US1122, P <0.001) costs than comparison subjects. In other words, the total cost was about 2-fold greater for OAG subjects than comparison subjects. Conclusions: We concluded that subjects with OAG had significantly higher utilization of all healthcare services than comparison subjects.